The spatial foundations of language and cognition - Mix, Kelly S.; Smith, Linda B.; Gasser, Michael (Oxford : Oxford University Press, 2010)
Presenting research on the role of space as a mechanism in language use and learning, experts from experimental psychology, computer science, linguistics, and researchers in child language consider the nature and applications of this research and its implications for understanding the processes involved in language acquisition.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Space and time in language; Space perception in children; Cognition in children; Child development; Language acquisition